Native Species in Barito Upstream at South Kalimantan, Indonesia: Sex Ratio and Length-Weight Relationship of Seluang Batang Fish (Rasbora argyrotaenia Blkr 1850) - Erwin Rosadi; Endang Yuli H.; Daduk Satyohadi; Gatut Bintoro (Center for Journal Management and Publication, 2016)
Freshwater potential in South Kalimantan is one million hectares and 140 species of fish are exploited. One of the fish resources in the intensive exploitation in South Kalimantan is Seluang Batang fish (Rasbora argyrotaenia). The purpose of this study was to obtain scientific data related to the sex ratio of fish and length-weight relationships of R. argyrotaenia in Barito upstream at South Kalimantan. The study was conducted in the Barito upstream in South Kalimantan, on location 2o57'36.10'' S 114o5'37.92'' E; 3o01'07.86